Vincristine Promotes Transdifferentiation of Fibroblasts Into Myofibroblasts via P38 and ERK Signal Pathways - Xu, Hui; Yang, Jingwen; Tu, Mengyun; Weng, Jie; Xie, Mengying; Zhou, Zhiliang; Zhou, Peisen; Wang, Liang; Chen, Chan; Wang, Zhiyi (Frontiers in Pharmacology, 2022)
Background: Vincristine (VCR) is used in the clinic as an anti-tumor drug. VCR can cause pulmonary fibrosis (PF), leading to respiratory failure. The transformation of fibroblasts into myofibroblasts may play a key role in PF. The present study attempted to reveal the molecular mechanism of VCR-induced PF and the possible involvement of the mitogen-activated protein kinase (MAPK) signaling pathway. Methods: Human embryonic lung fibroblasts (HELFs) were treated with different concentrations of VCR. Inhibitors of extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 MAPK were added to HELFs. Cell proliferation state was assessed using cell counting kit-8 and by directly counting the number of cells. The expressions of vimentin and α-smooth muscle actin (α-SMA) were investigated using western blot and immunofluorescence analyses. Activation of ERK and P38 was estimated by the expression of phosphorylated p38 MAPK (p-p38), p38 MAPK, phosphorylated ERK1/2 (p-ERK1/2) and ERK1/2 using western blot analysis. Enzyme-linked immunosorbent assay was used to estimate the level of collagen I in cell culture supernatants. Results: Results showed that VCR promoted cellular proliferation, secretion of collagen Ⅰ and the expression of vimentin and α-SMA. High expression of p-p38 and p-ERK1/2 was associated with the activation of the MAPK signaling pathway. MAPK inhibitors SB203580 and PD98059 suppressed the expression of the above proteins. Conclusion: Our study revealed that VCR could promote the differentiation of fibroblasts into myofibroblasts by regulating the MAPK signal pathway, which may be a promising way to treat VCR-induced PF.